An Act to Prevent Routs, Riots, and Tumultuous assemblies, and the Evil Consequences Thereof, reprinted in Cumberland Gazette (Portland, MA), Nov. 17, 1786, at 1 - (:unkn) unknown (General Publisher, 1786)
Prohibited being armed with a club or other weapon while rioting.
--
Keywords: CARRY - INTENT TO COMMIT CRIME